Waste Stream Porous Alkali Activated Materials for High Temperature Application - Bajare, Diana; Vitola, Laura; Dembovska, Laura; Bumanis, Girts (Frontiers in Materials, 2019)
The growing interest of using industrial waste as recycled raw materials for the production of new, innovative materials is associated with effective use of natural resources and circular (zero-waste) economy. The research object is waste stream materials coming from chemical and processing industries, such as aluminium scrap recycling waste, chamotte-like precursor, firebricks sawing residues, and their use in production of high-temperature resistant, porous insulation materials by using alkali activation technique with 6M NaOH solution. Adding aluminium scrap recycling waste to the composition of the tested alkali activated materials (AAM) contributed to the porous structure of the material with the pore size ranging from 1000 – 5000 µm (detected by Micro-XCT, SEM)). Lightweight (350-850 kg/m3) and heat-resistant (up to 1000°C) AAM with compressive strength from 1.0 to 3.0 MPa was obtained. The mineralogical composition of the obtained AAM was detected (XRD) and the heat resistant minerals in the structure of AAM were identified. It was concluded that the increased amount of Al2O3 in the raw material composition resulted in improved thermal stability of the AAM. In case where SiO2/Al2O3 ratio is <2, the formation of high-temperature resistant minerals, such as carnegeite and nepheline, was observed. The obtained AAM could resist up to 8 thermal shock cycles and it could be easily adapted to the industrial production and application such as thermal insulation layer in laboratory furnaces.